THE INFLUENCE OF COMPENSATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE - Saputra, Wahyu Marda (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to analyze the influence of compensation and work environment on employee performance both directly and indirectly through job satisfaction as an intervening variable. Method: This research uses quantitative research using an explanatory research approach. The sample in this research was 57 employees at CV. Mitra Gemilang Bersinar who were taken using saturated sampling. This research has seven hypotheses. Results: The results of the simultaneous test show that compensation and work environment influence job satisfaction. Then, compensation, work environment, and job satisfaction influence employee performance. The results of the hypothesis test also show that there are five paths that have a significant effect, namely compensation on employee performance of 0.449 with a significance value of 0.000, compensation on job satisfaction of 0.476 with a significance of 0.000, job satisfaction on employee performance of 0.274 with a significance value of 0.023, work environment on job satisfaction of 0.565 with a significance value of 0.000, and work environment on employee performance of 0.529 with a significance value of 0.000. Novelty: This research also proves two indirect paths showing the effect of compensation on employee performance through job satisfaction of 0.130 and the work environment on employee performance through job satisfaction of 0.154.